The indebtedness of Portuguese soccer teams - looking for determinants - Mourao, P. (Journal of Sports Sciences, 2012)
This work tests determinants of the indebtedness of Portuguese soccer teams using the sample of teams playing in the Portuguese major league from the 1999-2000 season until the 2005-2006 season. This is a major issue related to both the medium-term solvency of the Portuguese professional soccer sector and the solvency of the European soccer market. Our results show that past debt obligations, the market area, the rank of each team and, particularly, the costs of wages exert a positive and significant effect on the debt ratio for each soccer team. These results support suggestions seeking to promote the sustainability of the soccer sector, namely, the imposition of wage caps, a new regulation limiting the increasing debt ratios and the redistribution of TV rights via a more egalitarian system.